Noncanonical sortase‐mediated assembly of pilus type 2b in group B Streptococcus. Issue 11 (22nd July 2015) - Lazzarin, Maddalena; Cozzi, Roberta; Malito, Enrico; Martinelli, Manuele; D'Onofrio, Mariapina; Maione, Domenico; Margarit, Immaculada; Rinaudo, C. Daniela
ABSTRACT: Group B Streptococcus (GBS) expresses 3 structurally distinct pilus types (1, 2a, and 2b) identified as important virulence factors and vaccine targets. These pili are heterotrimeric polymers, covalently assembled on the cell wall by sortase (Srt) enzymes. We investigated the pilus‐2b biogenesis mechanism by using a multidisciplinary approach integrating genetic, biochemical, and structural studies to dissect the role of the 2 pilus‐2b‐associated Srts. We show that only 1 sortase (SrtC1‐2b) is responsible for pilus protein polymerization, whereas the second one (Srt2‐2b) does not act as a pilin polymerase, but similarly to the housekeeping class A Srt (SrtA), it is involved in cell‐wall pilus anchoring by targeting the minor ancillary subunit. Based on its function and sequence features, Srt2‐2b does not belong to class C Srts (SrtCs), nor is it a canonical member of any other known family of Srts. We also report the crystal structure of SrtC1‐2b at 1.9 Å resolution. The overall fold resembles the typical structure of SrtCs except for the N‐terminal lid region that appears in an open conformation displaced from the active site. Our findings reveal that GBS pilus type 2b biogenesis differs significantly from the current model of pilus assembly in gram‐positive pathogens.—Lazzarin, M., Cozzi, R., Malito, E., Martinelli, M., D'Onofrio, M., Maione, D., Margarit, I., and Rinaudo, C. D. Noncanonical sortase‐mediated assembly of pilus type 2b in group B Streptococcus. FASEB J. 29, 4629‐4640 (2015). www.fasebj.org